Oedipus 2.0: Rethinking Digital Subjectivity with Lacan and the Posthuman - Tamayo, Rance Jomill Z. (Animo Repository, 2022)
Succeeding the theoretical foundations of modernism and posthumanism, contemporary theories on digital subjectivity have been composed of various discourses concerning the subject as a dichotomy of either a corporeal or cybernetic entity. However, resting on this debate persists a conceptual stagnation; building on the seemingly opposite orders of Posthumanism and Lacanian Psychoanalysis, I develop the concept of Cyber-Oedipal subjectivization as a subversive alternative. Cyber-Oedipus is a becoming figure that synthesizes the composition of the inhuman core of the Oedipal structure and the rhizomatic virtuality of the posthuman flux. This subject is a patchwork project, rather than a fluctuating creature of the organic and technical material/world. Lacan’s work functions as the basis of the construction, but is mediated as a process through the conception of the posthuman by Katherine Hayles and Donna Haraway, ultimately becoming the triadic protean of cyberspace.